Genotoxicity of synthetic amorphous silica nanoparticles in rats following short-term exposure. Part 1: Oral route - Tarantini, Adeline (2015)
Synthetic amorphous silica (SAS) in its nanosized form is now used in food applications although the potential risks for human health have not been evaluated. In this study, genotoxicity and oxidative DNA damage of two pyrogenic (NM-202 and 203) and two precipitated (NM-200 and -201) nanosized SAS were investigated in vivo in rats following oral exposure. Male Sprague Dawley rats were exposed to 5, 10, or 20 mg/kg b.w./day for three days by gavage. DNA strand breaks and oxidative DNA damage were investigated in seven tissues (blood, bone marrow from femur, liver,spleen, kidney, duodenum, and colon) with the alkaline and the (Fpg)-modified comet assays, respectively. Concomitantly, chromosomal damage was investigated in bone marrow and in colon with the micronucleus assay. Additionally, malondialdehyde (MDA), a lipid peroxidation marker, was measured in plasma. When required, a histopathological examination was also conducted. The results showed neither obvious DNA strand breaks nor oxidative damage with the comet assay, irrespective of the dose and the organ investigated. Similarly, no increases in chromosome damage in bone marrow or lipid peroxidation in plasma were detected. However, although the response was not dose-dependent, a weak increase in the percentage of micronucleated cells was observed in the colon of rats treated with the two pyrogenic SAS at the lowest dose (5 mg/kg b.w./day). Additional data are required to confirm this result, considering in particular, the role of agglomeration/aggregation of SAS NMs in their uptake by intestinal cells.